Mortality and Respiratory-Related Hospitalizations in Idiopathic Pulmonary Fibrosis Not Treated With Antifibrotics - Cottin, Vincent; Spagnolo, Paolo; Bonniaud, Philippe; Nolin, Maëva; Dalon, Faustine; Kirchgässler, Klaus-Uwe; Kamath, Tripthi V.; Van Ganse, Eric; Belhassen, Manon (Frontiers in Medicine, 2021)
Background: Real-world data regarding outcomes of idiopathic pulmonary fibrosis (IPF) are scarce, outside of registries. The claims data from the French National Health System (SNDS) were used to describe outcomes in patients diagnosed with IPF in 2015-2016 but who did not receive antifibrotic therapies. Method: Patients aged <50 years were excluded, as were patients with pulmonary fibrosis other than IPF, patients who had previously received a lung transplant, and those who had received antifibrotic therapies at any time between 2010 and 2016. Patients were followed-up until their last health record, lung transplantation, initiation of antifibrotic therapies, death, or the end of the study period (31 December 2017), whichever occurred first. Results: A total of 5,360 patients (43.2%) not treated with antifibrotic therapies were included. The mean age was 75.5 years, and 57.9% were males. In the year before inclusion, 47.3% of patients had a Charlson score ≥5. During follow-up, 41.2% of patients died. The unadjusted incidence rate was 29.9 per 100 person-years (95%CI=[28.7-31.2]), and the cumulative incidence of death at three years was 50.2% (95% CI=[48.3%-52.1%]. In the study population, 35.3% of patients experienced an acute respiratory-related hospitalization. The unadjusted incidence rate was 32.1 per 100 person-years (95%CI=[30.6-33.5]) and the cumulative incidence of the event at three years was 41.5% (95% CI=[39.7%-43.2%]. Interpretation: This observational study showed that, if untreated with antifibrotics, IPF is associated with a 50% all-cause mortality at three years. These figures can serve as a historical control of the natural course of the disease.